The Relationship Between Career Thoughts and Adjustment for Individuals With Multiple Sclerosis. (January 2018) - Lustig, Daniel C.; Xu, Yonghong Jade; Strauser, David R.; MacKay, Michael M.
The study investigated the relationship between the psychosocial adjustment and dysfunctional career thoughts for adults with multiple sclerosis. The Reactions to Impairment and Disability Inventory measured psychosocial adjustment, and the Career Thoughts Inventory measured dysfunctional career thoughts. The results found that (a) higher levels of depression were associated with higher levels of decision-making confusion and commitment anxiety and (b) higher levels of adjustment were associated with lower levels of decision-making confusion. Rehabilitation counselor implications are discussed.